STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU TERHADAP HASIL BELAJAR SISWA DI SMA NEGERI 1 PEUKAN BADA ACEH BESAR - Eka Mayasari; Muhammad Syarif (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2018)
The Principal’s strategy is the important factor for determining the succesfull of increasing teacher’s competency. The aims of this study  was to know the program, implementation, evaluation and obstacle that’s faced by principal of SMA Negeri  1 Peukan Bada Aceh Besar. This research was conducted by descriptive qualitative methode. the data were collected by observation, interview adn documenation technique. The subcject of this research was a principal, vice of principal and teachers. The data was analyzed by data reduction,data display, drawing conclusion and data verification. The result shown that (1) The program of the principal for increasing teacher’s competency in SMA Negeri  1 Peukan Bada Aceh Besar was prepared by team of school develpoment in the beginning of the semester or the school year which is including annual program, semester program and it has been documented well. Commonly it relates to the quality of learning that always start with lesson plans ( RPP). (2) The implementation of the program for increasing teacher’s competency in SMA N 1 Peukan Banda Aceh Besar was started by presenting the instruction on the beginning of each semester. In implementing the strategy of school management, the principal/ school was applying kinship’s principle, however teachers who can increase their competency, they will get reward, and the teacher who are less in their competency, they will get reproof. (3) the evaluation of principal for increasing teacher’s competency was carried out at the end of each semester through the assessment of teacher’s performance that’s described in SKP, (4)the obstacle of principal for increasing teacher’s competency was include lack of teacher’s awareness in upholding discipline and low disciplines of both tecahers and the students.